Precise tip positioning of a flexible manipulator using resonant control - Mahmood, Iskandar Al-Thani; Moheimani, S. O. Reza; Bhikkaji, Bharath (Institute of Electrical and Electronics Engineers ( IEEE ), 2008)
A single-link flexible manipulator is fabricated to represent a typical flexible robotic arm. This flexible manipulator is modeled as an SIMO system with the motor torque as the input and the hub angle and the tip position as the outputs. The two transfer functions are identified using a frequency-domain system identification method, and the resonant modes are determined. A feedback loop around the hub angle response with a resonant controller is designed to damp the resonant modes. A high-gain integral controller is also implemented to achieve zero steady-state error in the tip position response. Experiments are performed to demonstrate the effectiveness of the proposed control scheme.